Sustainability of Omnichannel in Banks with Online Service Strategy and Pricing Decisions: Keberlanjutan Omnichannel di Bank dengan Strategi Layanan Online dan Keputusan Harga - Indayani, Lilik; Hariasih, Misti; Prapanca , Detak; Mariani, Anti; Mahendra, Danar Putra (Indonesian Journal of Law and Economics Review, 2023)
This quantitative research explores the optimization of omnichannel banking strategies in conventional Banks in East Java, Indonesia. With a focus on 17 member Banks from the Indonesian Banking Association in the Sidoarjo region, this study aims to analyze the impact of online services (64%) and pricing decisions (34%) on the sustainability of omnichannel initiatives. By connecting all marketing channels on a unified platform, Banks can deliver consistent customer experiences, fostering exceptional closeness and satisfaction leading to enhanced loyalty. However, the lack of awareness among customers about the top management's applied strategies poses a serious challenge in this program. The implications of diverse information, as well as online service and pricing decisions, play a crucial role in the success of the Omnichannel Banking program. The findings of this research provide valuable insights for global scientists and practitioners seeking to leverage omnichannel strategies for sustainable customer engagement in the banking sector. Highlights: Customer-Centric Approach: Omnichannel banking enables a unified customer experience across all platforms, fostering exceptional closeness and satisfaction, leading to enhanced loyalty and retention. Optimizing Online Services: The study reveals that effective online services contribute significantly (64%) to the sustainability of omnichannel strategies, emphasizing the importance of seamless digital interactions. Strategic Pricing Decisions: The research highlights the critical role of pricing decisions (34%) in shaping the success of omnichannel initiatives, emphasizing the need for a well-balanced pricing strategy to drive customer engagement and business growth. Keywords: Omnichannel Banking, Sustainable Strategies, Customer Engagement, Online Services, Pricing Decisions.